METHODOLOGICAL ASPECTS OF HISTORICAL AND PEDAGOGICAL RESEARCHES - Victor V. Lobanov (Moscow Polytechnic University, 2016)
This article highlights some aspects of historical and educational research from the standpoint of methodology. It contains the results of the study of dissertations' methodological framework on the history of education and pedagogical thought performed in modern Russia. The authors analyzed the problem of formulating the relevance, objectives and hypotheses for this kind of work, recommendations on improving the quality of research procedures in order to increase the validity of research results.